Kritikan Liberal Terhadap Institusi Islam Dalam Wacana Negara Sekular: Satu Penelitian Awal - Muhammad Rashidi Wahab; Wan Adli Wan Ramli; Wan Mohd Azam Mohd Amin; Mohd Faizul Azmi; Wan Haslan Khairuddin; Redwan Yasin; Nur Ayuni Mohd Isa; Muhammad Khairi Mahyuddin (Majlis Agama Islam Selangor, 2024)
Non-Indexed Publication